Створення безпечних локальних мереж з використанням елементів штучного інтелекту - Тяптя, А. В. (ХНУРЕ, 2024)
An analysis of the principles of creating secure local networks using advanced information security technologies was carried out. The key directions in the field of security technologies of local networks are considered. Correct use of encryption technologies, network firewalls, identification and authentication systems, but care must be taken to ensure that the cost of security does not exceed reasonable limits.
Keywords: безпечна локальна мережа; secure local networks